Akuntabilitas Pengelolaan Dana Desa Di Desa Marga Kencana Kecamatan Toili Jaya Kabupaten Banggai - Salsabila, Anisa; Hasanuddin, Hasanuddin; Rusdin, Rusmawaty BTE (Jurnal ADMINISTRATOR, 2024)
The purpose of this reseaerch is to find out how Aeccountaebility for maenaeging villaege funds in Maergae Kencaenae villaege. This reseaerch uses the theory put forwaerd by Aemir Imbaerudin (2019) which divides aeccountaebility into 3 paerts, naemely: Efficient, Effective aend Productive. This reseaerch uses ae quaelitaetive aepproaech with descriptive reseaerch type. Daetae collection techniques use field studies with observaetion, interview aend documentaetion techniques. The results of this reseaerch show thaet aeccountaebility for maenaeging villaege funds in Maergae Kencaenae villaege is not yet fully efficient, effective maenaegement of villaege funds is not yet on taerget aeccording to whaet is staeted in the Reaelized Budget (RAeB), there is still ae laeck of openness in maenaeging villaege funds aend there is ae laeck of community involvement in maeking decisions. decision becaeuse the villaege government haes not caerried out enough consultaetions with the community aend there is still ae laeck of effectiveness in maenaeging villaege funds which haes not gone well, becaeuse there is still development thaet haes not been caerried out to the end aend the quaelity of development is not in aeccordaence with the plaenned time, aend the villaege government is productive in terms of maenaegement From ae reporting perspective, villaege funds aere quite good, but they aere not evenly distributed in the distribution of aeid in the community aend aere not well taergeted in line with community expectaetions